Pagar Alam City Cultural Tourism Development Strategy - Wita Hariani; Yohane Susanto (Utan Kayu Publishing, 2024)
This research aims to find out what is the right strategy to develop cultural tourism in the city of Pagar Alam, by identifying and analyzing cultural tourism development strategies in the area. The techniques used in this research are qualitative descriptive and SWOT analysis. To collect data in the field the author carried out observations, interviews and documentation. The aim of this research is to increase public awareness about Pagar Alam culture, increase the quantity and quality of tourists coming to the area, increase regional income and increase the community's ability to develop cultural tourism.